Marketing Mix Strategy of Certified Palm Oil Seedling in Bungo Regency - Supriyati Supriyati; Amran Amran; Khairun A. Roni (Baselang, 2021)
The study aims to analyze the marketing mix strategy of certified palm oil seedlings. The method used was descriptive qualitative by describing and interpreting marketing strategy using marketing mix concept. Formulating a certified palm oil seed marketing strategy based on an assessment of the role of variables in the marketing mix implemented. The product strategy was expected to maintain the quality of certified palm oil seedlings. In the pricing strategy was to increase the price compliance with the quality of certified palm oil seedlings and apply discounts for consumers, especially small farmers. For the distribution line mix strategy should be able to shorten the distribution channel of certified palm oil seedlings and supervise the distribution process to the hand of farmers. Then, implementing a promotional mix strategy with more publicized promotional activities and expanding the dissemination of information on certified palm oil seedlings.